Blended Learning Model and PAI Learning Challenges In The Society 5.0 Era at MTsN Blora - Musthoifiyah, Ainy; Miftah, Muhammad (LP2M IAIN kUDUS, 2023)
This study analyzes the blended learning learning model with a background from the Covid'19 pandemic incident which resulted in the formation of learning methods by combining conventional and modern learning, namely conducting face-to-face learning in electronic-based networks. The purpose of this study is to describe the blended learning model in PAI lessons that has been carried out at MTs N Blora in the midst of the co-19 pandemic. The method used in this study is descriptive qualitative which comes from teachers in the field of PAI and several students who were selected purvosively. The data is obtained from being able to use observation and interview techniques. This research can create new references regarding learning methods that are more creative and innovative, because blended learning is a learning model that is not monotonous and students here don't only listen to lectures, but they also explore expertise in the field of information and technology (IT) through applications. So that the co-19 pandemic can create new breakthroughs in the world of education. The results of this study are to be able to find out the differences between offline and during learning, the implementation of blended learning at MTs N Blora is done by utilizing the Google Form, Google Class, Google Meet and Zoom meating